Does invasive Chondrostoma nasus shift the parasite community structure of endemic Parachondrostoma toxostoma in sympatric zones? - Simková, Andrea; Navrátilová, Petra; Dávidová, Martina; Ondračková, Markéta; Sinama, Melthide; Chappaz, Rémi; Gilles, André; Costedoat, Caroline (Parasites & vectors, 2012)
BACKGROUND: The composition of parasite communities in two cyprinid species in southern France - native and threatened Parachondrostoma toxostoma and introduced Chondrostoma nasus - was investigated. In sympatry, these two species form two hybrid zones in the Durance and Ardeche Rivers. Due to their different feeding preference and habitat positions in allopatry, we supposed a difference in parasite communities between fish species. We expected more similar parasite communities in sympatric zones associated with habitat overlap (facilitating the transmission of ectoparasites) and similar feeding (more generalist behaviour when compared to allopatry, facilitating the transmission of endoparasites) in both fish species. Finally, we investigated whether P. toxostoma x C. nasus hybrids are less parasitized then parental species. METHODS: One allopatric population of each fish species plus two sympatric zones were sampled. Fish were identified using cytochrome b gene and 41 microsatellites loci and examined for all metazoan parasites. RESULTS: A high Monogenea abundance was found in both allopatric and sympatric populations of C. nasus. Trematoda was the dominant group in parasite communities of P. toxostoma from the allopatric population. In contrast, the populations of P. toxostoma in sympatric zones were parasitized by Dactylogyrus species found in C. nasus populations, but their abundance in endemic species was low. Consequently, the similarity based on parasite presence/absence between the sympatric populations of P. toxostoma and C. nasus was high. Sympatric populations of P. toxostoma were more similar than allopatric and sympatric populations of this species. No difference in ectoparasite infection was found between P. toxostoma and hybrids, whilst C. nasus was more parasitized by Monogenea. CONCLUSIONS: The differences in endoparasites between P. toxostoma and C. nasus in allopatry are probably linked to different feeding or habitat conditions, but host-parasite evolutionary associations also play an important role in determining the presence of Chondrostoma-specific monogeneans. Our findings suggest that Dactylogyrus expanded with the source host C. nasus into introduced areas and that P. toxostoma became infected after contact with C. nasus. Although the genotype of P. toxostoma and recombinant genotypes of hybrids are susceptible to Dactylogyrus transmitted from C. nasus, the intensity of infection is low in these genotypes.
Keywords: Parasites; společenstvo; Animals; France; Cyprinidae; paraziti; zvířata; Biota; Francie